Regional differences in ischemic stroke in India (north vs. south). Issue 7 (October 2019) - Venugopalan, Vishnu Y; Bhatia, Rohit; Pandian, Jeyaraj; Khurana, Dheeraj; Kaul, Subhash; Sylaja, P.N.; Arora, Deepti; Khatter, Himani; Padma, M.V.; Singhal, Aneesh B.
Background: India is a large country with geographically diverse populations and varying risk factors. Identification of regional differences can improve healthcare policy decisions. Aim: To study regional differences in stroke between North and South India. Methods: We analyzed data from the Indo-US Collaborative Stroke Project, a National Institute of Health-funded multicentre prospective study conducted in five academic centers in India with a US-based coordinating center. Risk factors, severity, mechanisms, management, complications, and outcomes among ischemic stroke patients were compared between North and South Indian centers. Results: Of the 2066 patients enrolled from North ( n = 1060) and South India ( n = 1006), North Indian patients were significantly older with fewer men and had lower rates of diabetes (32.8% vs. 38.7%, p < 0.01), dyslipidemia (3.5% vs. 25.7%, p < 0.01), tobacco use (27% vs. 38%, p < 0.001), and alcohol use (30.1% vs. 38.6%, p < 0.01). North Indian patients had higher median National Institute of Health stroke scale scores (10 vs. 9, p < 0.01), more frequent large-artery atherosclerosis mechanism (34% vs. 25.6%, p < 0.001), intravenous thrombolysis (14.0% vs. 6.1%, p < 0.001), and lower rates of pneumonia (10.5% vs. 15.1%, p = 0.02). The three-month outcome (modified Rankin Scale score 0–2, 45.8% vs. 50.3%, p = 0.08) did not differ; however, North Indian patients had higher 90-day mortality (23.5% vs. 13.5%, p < 0.0001). Conclusions: The substantial regional differences in stroke risk factors and mechanisms may be partly explained by factors such as differing dietary habits and lifestyle, which can be addressed at a national level. Differences in acute and inpatient stroke care suggest a need for better adoption of national stroke management guidelines.